Preparation and Evaluation of a Powdered Rebamipide Mouthwash as In-Hospital Formulation: Considering Dispersion before Use in Patients - Naoko Ishii; Senri Mizobuchi; Yayoi Kawano; Takehisa Hanawa (MDPI AG, 2021)
In Japan, rebamipide (RB) mouthwash (RB-MW) for oral mucositis induced by cancer chemotherapy has been prepared using in-hospital formulation. Usually, RB-MW is prepared by dispersing crushed commercial RB tablets in the dispersion medium; however, uniformity is difficult to obtain due to low solubility. The current study aims is to prepare homogenously dispersed formulations using the fine particles of crushed tablets by a method that is convenient for hospital use. Commercial RB tablets were pre-milled at different milling times as "RB-Ts". A ground mixture was then prepared by co-grinding the RB-Ts with HPC-L or PVP K30 via a benchtop ball milling machine (MM400). The physicochemical properties of samples were evaluated for PXRD, FTIR, turbidity, particle size, and solubility. Although the milling of RB tablets decreased the crystallinity, the length of milling time did not affect them. In contrast, grinding using MM400 significantly decreased RB crystallinity; their PXRD patterns showed a halo, suggesting the amorphization of RB crystals by grinding. Although solubility and turbidity seemed to be affected by the type of polymer rather than the particle size, every ground mixture showed high dispersibility. Thus, grinding the RB-Ts with polymers appeared to be the most promising way to obtain stable dispersion as an in-hospital formulation.